PERENCANAAN MESIN PENGEROLL LAPISAN SANDAL MENGGUNAKAN MOTOR LISTRIK DENGAN SISTEM SEMI-OTOMATIS SKALA HOME INDUSTRY - Muhamad Fatoni (UNIVERSITAS ISLAM MALANG, 2019)
In the current era, the development of technology has helped many people, especially to facilitate the work that arises in life with new discoveries in the field of technology. Permaslahan which often arises in the process of rolling the slipper layer is still using manual or human power systems, which are less effective and can take time which is old. Therefore, the authors make